The Impact of Service Liberalization on Manufacturing Productivity in Indonesia - Wulan Oktabriyantina; Maddaremmeng Andi Panennungi (Department of Development Economics, Universitas Sriwijaya, 2021)
This study examined the impact of service liberalization on manufacturing productivity firms in Indonesia through mode three (commercial presence) during 2006–2014. It used firm-level data sourced from the manufacturing census published by the Indonesian Bureau of Statistic (BPS). To address the problem of endogeneity in service reform, this research uses an Instrumental Variables (IV) estimation of the fixed-effect model variety and utilized two types of data (FDI and STRI OECD) to compare the result. The findings show that service liberalization in Indonesia has a positive impact on manufacturing productivity at the firm level. Furthermore, this study estimates each service sector (e.g., electricity, gas, and water; construction; transportation, warehouse, and telecommunication), the results indicated that each service had a significant impact on improving firm performance. This research suggests that reducing restrictions on the service market will improve manufacturing productivity.